Predictors of Perinatal Mortality Associated with Placenta Previa and Placental Abruption: An Experience from a Low Income Country - Yifru Berhan (Hindawi Limited, 2014)
A retrospective cohort study design was used to assess predictors of perinatal mortality in women with placenta previa and abruption between January 2006 and December 2011. Four hundred thirty-two women (253 with placenta previa and 179 with placental abruption) were eligible for analysis. Binary logistic regression, Kaplan-Meier survival curve, and receiver operating characteristic (ROC) curve were used. On admission, 77% of the women were anaemic (<12 gm/dL) with mean haemoglobin level of 9.0 ± 3.0 gm/dL. The proportion of overall severe anaemia increased from about 28% on admission to 41% at discharge. There were 50% perinatal deaths (neonatal deaths of less than seven days of age and fetal deaths after 28 weeks of gestation). In the adjusted odds ratios, lengthy delay in accessing hospital care, prematurity, anaemia in the mothers, and male foetuses were independent predictors of perinatal mortality. The haemoglobin level at admission was more sensitive and more specific than prematurity in the prediction of perinatal mortality. The proportion of severe anaemia and perinatal mortality was probably one of the highest in the world.